The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/ncomms11074
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane calcium ATPase 4 signalling in cardiac fibroblasts mediates cardiomyocyte hypertrophy

Abstract: The heart responds to pathological overload through myocyte hypertrophy. Here we show that this response is regulated by cardiac fibroblasts via a paracrine mechanism involving plasma membrane calcium ATPase 4 (PMCA4). Pmca4 deletion in mice, both systemically and specifically in fibroblasts, reduces the hypertrophic response to pressure overload; however, knocking out Pmca4 specifically in cardiomyocytes does not produce this effect. Mechanistically, cardiac fibroblasts lacking PMCA4 produce higher levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 45 publications
1
82
0
Order By: Relevance
“…Mice (male only, n = 26) with complete inactivation of Atp2b4 have been generated and described elsewhere (15,16). The mice are in mixed background of 129/sv × C57BL/6.…”
Section: Methodsmentioning
confidence: 99%
“…Mice (male only, n = 26) with complete inactivation of Atp2b4 have been generated and described elsewhere (15,16). The mice are in mixed background of 129/sv × C57BL/6.…”
Section: Methodsmentioning
confidence: 99%
“…Using a number of mouse models in which PMCA4 was deleted globally, or specifically from the cardiomyocytes or from the fibroblasts, we demonstrated that PMCA4 is involved in the development of pathological cardiac hypertrophy by regulating Ca 2ϩ signaling in cardiac fibroblasts which in turn is essential in the regulation of cardiac hypertrophy (242). Total PMCA4 knockout and deletion of PMCA4 specifically from the fibroblasts protected the animals against pressure overload-induced cardiac hypertrophy, but this protection was not evident when PMCA4 was deleted specifically from the cardiomyocytes.…”
Section: Pmca and The Heartmentioning
confidence: 99%
“…Total PMCA4 knockout and deletion of PMCA4 specifically from the fibroblasts protected the animals against pressure overload-induced cardiac hypertrophy, but this protection was not evident when PMCA4 was deleted specifically from the cardiomyocytes. Ablation of PMCA4 from cardiac fibroblasts led to an increase in [Ca 2ϩ ] i which subsequently increased secreted frizzled related protein 2 (sFRP2) transcription, an inhibitor of the Wnt signaling pathway known to be protective against injury of the myocardium (151,242). Secretion of sFRP2 from PMCA4 ablated fibroblasts then acted in a paracrine fashion to reduce cardiomyocyte hypertrophy and confer protection against the development of heart failure.…”
Section: Pmca and The Heartmentioning
confidence: 99%
“…The increased deposition of extracellular matrix proteins including collagens deteriorate diastolic function by increasing ventricular stiffness and reducing electrical connectivity (7,8). Myofibroblasts also secrete a variety of chemokines that increase inflammation through the recruitment of circulating lymphocytes (9,10).…”
mentioning
confidence: 99%